Enhanced Production of Exo-Polygalacturonase by Fusarium solaniin Solid-State Fermentation - Hamid, Saunia; Nawaz Bhatti, Haq; Abdul Qayyum, Uzma (Asian Journal of Chemistry, 2010)
Fungal pectinases are among the most important enzymes with major applications in food and drinking industries. In the present investigation the feasibility of using orange peel for the production of exopectinase by Fusarium solani in solid-state fermentation has been evaluated. Optimization of process parameters was carried out for enhanced production of the enzyme. Maximum exopectinase activity of 102.21 ± 6.13 U/g of dry orange peel was achieved under optimum growth conditions. The optimum conditions were: initial moisture content of orange peel, 60 % (v/w); pH of the medium, 6.0; incubation temperature, 35 ± 1 ºC; amount of orange peel, 10 g and incubation period, 96 h. Addition of glucose (1 %) as carbon and energy additive and peptone (1 %) as nitrogen additive further enhanced the production of exopectinase.